The Contestability Paradigm in the Presence of Vertical Differentiation. Efficiency Evaluation of a Natural Oligopoly - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
This paper addresses the link between Contestable Markets and Natural Oligopolies, both considered as a reinterpretation of Bertrand' s Competition. A market with ex ante uncertainty as regards to technology is outlined. Technological uncertainty is solved by a pioneer entering the market with a high quality product. The high quality choice is a precommitment that affects market' s ex post contestability degree, which becomes endogenous; moreover, interacting with consumers' preferences about quality, this choice creates a barrier to entry. Thus, in a pure vertical differentiation case, and assumed that the cost curve is flat enough, the number of firnis enjoying positive market shares and positive profits turns out to be limited. This outcome seems to hold in the presence of experience goods as well, although here consumers may prefer to buy from entrants if good' s desirability is high. The model also suggests the possibility of an efficiency evaluation of an oligopoly with vertically differentiated products, in terms of a tradeoff between price and quality or variety.
Keywords: 330